Pengaruh Sertifikasi Halal Terhadap Keputusan Pembelian Produk Skincare the Saem di Desa Muara Bakti - Amelia, Siska; Noviarini, Tiara; Lestari, Hardita Amalia Sri Ayu (Jurnal Ilmiah Wahana Pendidikan, 2024)
The demands of the contemporary world are increasingly diverse. Nowadays, many women consider skincare to be their most important need. Despite the fact that many Muslim women buy skincare products in Indonesia, they often overlook this halal component. While halal is an important consideration when choosing a product, some shoppers only think about how much they like the product. This also happens in Muara Bakti Village, where the majority of people identify themselves as Muslims but there is still a low level of understanding of the importance of halal certification. The purpose of this study is to ascertain how halal certification affects consumers' decision to buy SAEM skincare products in Muara Bakti village. Using 88 respondents as a sample, this study uses a direct random sampling technique. Among the techniques for data analysis is validity